الجـامعة والبناءالاجتماعي - عمار, رواب; صباح, غربي (دفـاتر المـــــــــــخبـر, 2018)
ملخـص: لقد كانت الجامعة وما تزال مركزا للإشعاع الفكري وقطبا فاعلا في تغيير المجتمعات وتطويرها. فمصير الأمم الكبيرة يرتبط دون شك في جزء كبير منه بنجاعة النظام التربوي والجامعي، ولا تمثل القوة الاقتصادية والاجتماعية سوى الانعكاس لجامعة كقوة وقادرة على لعب دورها كقاعدة أساسية لكل حركية تغيير ودافع لكل تقدم حضاري باعتبار العملية التعليمية – التعلمية-في الجامعة نسق مفتوح، يشكل كل من الأستاذ والطالب طرفا مهما فيها، فإن أخذ ما يعبر عنه من آراء وما يزود به من معلومات بعين الاعتبار يجعل عملية التقويم أكثر شمولية وأكثر فعالية، وهذا ما سنتطرق له في هذا المقال. Abstract :   The University had been and she/you is still a center for the intellectualradiation and an active pole then in change of the societies and her development. Then a fate of the big nations is bind undoubtedly in big part from him by the educative system usefulness and the collegiate, and not assimilation of the economic strength and the sociability evened the reversal forUniversity and capable on I/we played a role like fundamental rule for each strategy change and an impulse for each civilized progress. With respect to the educational operationin the University an opened order, whatsoever is dubious the teacher and the student blinked no matter what in her, if he starts to express him from the views and what he steps up the information’s by him by eye of the considering the most inclusion and the most efficiency make the operation of the evaluation, and this will treat of him in this article